The intended and unintended impacts of a merit-based financial aid program for the poor : the case of ser pilo paga (2017)
We study a recent merit-based financial program for the poor in Colombia. We exploit sharp eligibility rules in household wealth and standardized test scores to identify the causal effect of financial aid on postsecondary enrollment and academic performance. We find large positive effects on postsecondary enrollment on both the extensive and intensive margins. Immediate enrollment doubled among eligible students, making the SES gap in enrollment disappear among top students. At the intensive margin, the program shifted students from low-quality institutions into higher-quality institutions, and from public to private colleges. We also observe significant general equilibrium effects in secondary and postsecondary education. The program promoted class diversity at top private schools, and significantly raised student quality at these institutions (but not public institutions). Demand for top private education shifted to the right, driving admission rates downward and increasing entry competition at these institutions, thus raising stratification by ability. However, program beneficiaries did not fully crowd out high-SES students from top private schools because supply also expanded. Finally, the program seems to have raised high school exit test performance among recent cohorts with relatively poor backgrounds.